2018
DOI: 10.1016/j.combustflame.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and mechanistic investigation of benzene formation during atmospheric pressure flow reactor oxidation of n-hexane, n-nonane, and n-dodecane below 1200 K

Abstract: As a consequence a detailed in-house reaction model, which was already extensively validated against global combustion characteristics, has been tested against the measured speciation data. The model succeeds in reproducing all the measured species and is in good agreement with the measurements. This study identifies the major paths during the oxidation of all three fuels studied and provides valuable database and insight into the product spectrum and prediction of soot precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 74 publications
3
30
0
Order By: Relevance
“…67 Due to the change in temperature, Reynolds numbers vary from 113-161, which assures the plug flow approximation; also, the residence time of gas ranges from 1.2-1.8 s. 66 The experimental and numerical methods have been shown to give valid targets for development of kinetic mechanisms. [67][68][69][70] A brief summary of the experimental conditions may be found in Table 1; the original publication gives more details. 3 For the present study, the full dataset was reanalyzed with respect to soot precursors and aromatic species.…”
Section: Methodsmentioning
confidence: 99%
“…67 Due to the change in temperature, Reynolds numbers vary from 113-161, which assures the plug flow approximation; also, the residence time of gas ranges from 1.2-1.8 s. 66 The experimental and numerical methods have been shown to give valid targets for development of kinetic mechanisms. [67][68][69][70] A brief summary of the experimental conditions may be found in Table 1; the original publication gives more details. 3 For the present study, the full dataset was reanalyzed with respect to soot precursors and aromatic species.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of soot in flames is described by formation, growth, and oxidation of polycyclic aromatic hydrocarbons (commonly known as PAHs) that are dependent on the temperature and on the combustion intermediates forming them [53,54]. The formation of PAHs is initiated by the emergence of aromatic rings from smaller hydrocarbon intermediates such as C 2 H 2 , C 2 H 4 , C 3 H 3 [53,54], the routes are function of temperature [55]. It has been observed that soot levels in flames are proportional to benzene concentrations but not to acetylene levels [40].…”
Section: Background -Fuel Property Effects On Soot Emissionmentioning
confidence: 99%
“…Soot oxidation is investigated under well-controlled conditions in a high-temperature flow reactor, which was also used for mass spectrometric studies of the chemical gas-phase kinetics of single compounds (Kathrotia et al, 2018;Oßwald et al, 2017) and technical fuels (Köhler et al, 2018). The new soot oxidation experiment consists of five key elements: (1) A flat-flame McKenna burner as the soot source, (2) a Dekati diluter to sample flame gases and soot particles directly from the flame, (3) the high-temperature flow reactor for soot oxidation at well-controlled conditions, (4) a particle sizer to measure the particle size distribution (PSD) before (reactor inlet) and after (reactor outlet) passing a distinct temperature profile in the reactor, and (5) a molecular-beam mass spectrometer to quantify both small molecular species originated from the sampled flame and oxidation products.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure described by Oßwald and Köhler (2015) compensates thermal inertia and systematic deviations of the oven temperature reading. The resulting profiles can be directly used as input for a zero-dimensional flow reactor simulation (Kathrotia et al, 2018) and respective results may be compared to the experimental value at the respective temperature.…”
Section: Temperature Profilesmentioning
confidence: 99%